Educational Influence With Role Play About First Aid Rice In Sports Injury Ankle Sprain On Student Knowledge School - Imardiani; Ryikca Nurjayanti; Siti Romadoni (Jurnal Inspirasi Kesehatan, 2023)
Background: Injuries are damage to the body which results in pain, heat, redness, swelling and unable to function properly. Injuries often occur in school-age children due to excessive activity so they tend to experience ankle sprain problems . Sprains or ankle sprains are types of injuries that occur as much as 36.1% of other injuries. RICE first aid knowledge is very much needed in the initial management of injuries so that no more serious injuries occur. Selection of media with role play so as to help students improve their understanding of RICE first aid . Research Objectives: To know the effect of education with role play about RICE first aid sports injuries to ankle sprains on the knowledge of school students. Research Method: Type of quantitative research with Pre-Experimental One Group Pre-Test and post- Test Design , taking samples using a total sampling technique of 40 respondents. Providing knowledge using the role play method results in knowledge using a questionnaire. The results of the analysis using the Wilcoxon test . Research Results: Obtained the value of knowledge before being given education 13.00 and after being given education 20.00 with a p-value <0.05. Conclusion: There is an effect of education with role play about RICE first aid for sports injuries to ankle sprains on the knowledge of school students.